Providing depth information in the display for pursuit and compensatory tracking and optimization in 3‐D space. (7th January 2016) - Liu, Hongyan; Sun, Mengdan; Ye, Haili; Wang, Duming; Ge, Liezhong
Abstract: Objective: The formats of tracking displays exert important influences on tracking performance. Few previous studies explored the 3‐D tracking display formats. The present study aimed to construct the 3‐D formats for the manual pursuit and compensatory tracking displays by adding the depth information. Based on the results of tracking performance, we further optimized the preferable tracking format. Method: Three experiments were conducted. Experiment 1 was a confirmatory experiment to compare the effects of the two display formats on 2‐D manual tracking performance with previous studies. Experiment 2 extended the investigation to a 3‐D display by adding a depth cue indicating the relative size of the control marker and target. Experiment 3 was an optimisation experiment in which an improved 3‐D tracking display was modified, i.e., an extra depth cue was complemented to clearly signify the relative position of the target and the control marker. Results: Pursuit tracking performance was better than compensatory tracking performance in both 2‐D (Experiment 1) and 3‐D space (Experiment 2). It also found that the extra depth cue significantly improved the tracking success rate and the subjective satisfaction of the pursuit display format in 3‐D space (Experiment 3). Conclusions: These findings indicated that the depth cues could be used in tracking display in 3‐D space and have important implications for the design of some motor training and tracking systems.